Centralizing neurofibromatosis experimental tool knowledge with the NF Research Tools Database. (23rd June 2022) - Clayton, Ashley; DeFelice, Mialy; Zalmanek, Brynn; Hodgson, Jay; Morin, Caroline; Simon, Stockard; Bletz, Julie A; Eddy, James A; Nikolov, Milen; Banerjee, Jineta; Vinnakota, Kalyan; Marasca, Marco; et al.
Abstract: Experimental tools and resources, such as animal models, cell lines, antibodies, genetic reagents and biobanks, are key ingredients in biomedical research. Investigators face multiple challenges when trying to understand the availability, applicability and accessibility of these tools. A major challenge is keeping up with current information about the numerous tools available for a particular research problem. A variety of disease-agnostic projects such as the Mouse Genome Informatics database and the Resource Identification Initiative curate a number of types of research tools. Here, we describe our efforts to build upon these resources to develop a disease-specific research tool resource for the neurofibromatosis (NF) research community. This resource, the NF Research Tools Database, is an open-access database that enables the exploration and discovery of information about NF type 1-relevant animal models, cell lines, antibodies, genetic reagents and biobanks. Users can search and explore tools, obtain detailed information about each tool as well as read and contribute their observations about the performance, reliability and characteristics of tools in the database. NF researchers will be able to use the NF Research Tools Database to promote, discover, share, reuse and characterize research tools, with the goal of advancing NF research. Database URL : https://tools.nf.synapse.org/ .